The Clinical Impact of CLIR Tools toward Rapid Resolution of Post-Newborn Screening Confirmatory Testing for X-Linked Adrenoleukodystrophy in California - Hao Tang; Jamie Matteson; Piero Rinaldo; Silvia Tortorelli; Robert Currier; Stanley Sciortino (MDPI AG, 2020)
Since the start of X-linked adrenoleukodystrophy (ALD) newborn screening in California, more than half of the diagnosed cases were found to have an ATP binding cassette subfamily D member 1 (ABCD1) gene variant of uncertain significance (VUS). To determine retrospectively the likelihood that these were true positive cases, we used a web-based post-analytical tool in Collaborative Laboratory Integrated Reports (CLIR). Confirmatory plasma very long-chain fatty-acids (VLCFA) profiles for ALD screen positive infant boys were run through the CLIR ALD tool. We compared the distribution by ABCD1 variant classification (pathogenic, likely pathogenic, VUS, and no variant) with the CLIR tool score interpretation (non-informative, possibly ALD, likely ALD, and very likely ALD) and the current case diagnosis. The study showed that CLIR tool positive interpretations were consistent with 100% of the pathogenic and likely pathogenic variants on the ABCD1 gene if a more conservative guideline was used. The tool interpretations were also consistent with screened cases that were determined to not have disease (our no-disorder group). The CLIR tool identified 19 diagnosed ALD cases with VUS to be potential false positives, representing a 40% reduction among all diagnosed ALD cases with VUS. The reduction could be extended to 65% if a more aggressive threshold was used. Identifying such preventable false positives could alleviate the follow-up burden for patients, their families, and California Special Care Centers.